On the Treatment of Non-Original Sample Members in the German Household Panel Study (SOEP): Tracing, Weighting, and Frequencies - Martin Spieß; Martin Kroh; Rainer Pischner; Gert G. Wagner (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
In this paper we discuss the rationale for tracing non-original sample members (Non-OSMs) in household panel studies, and in particular in SOEP, and the implications for weighting. We present results on the incidence, survival rates, and thus the relevance of Non-OSMs in the SOEP
Keywords: 330